Feminist judgments : reproductive justice rewritten / edited by Kimberly M. Mutcherson. - Mutcherson, Kimberly M., 1972- (Feminist judgments series., 2020)
Reproductive justice (RJ) is a pivotal movement that supplants the language and limitations of reproductive rights. RJ's tenets are that women have the human rights to decide if or when they'll become pregnant, whether to carry a pregnancy to term, and to parent the children they have in safe and healthy environments. Recognizing the importance of the rights at stake when the law addresses parenting and procreation, the authors in this book re-imagine judicial opinions that address the law's treatment of pregnancy and parenting. The cases cover topics such as forced sterilization, pregnancy discrimination, criminal penalties for women who take illegal drugs while pregnant, and state funding for abortion. Though some of the re-imagined cases come to the same conclusions as the originals, each rewritten opinion analyzes how these cases impact the most vulnerable populations, including people with disabilities, poor women, and women of color.